Time motion and notational analysis of 21 point and 15 point badminton match play - Ming, C. L.; Keong, C. C.; Ghosh, A. K. (International Journal of Sports Science and Engineering, 2008)
The purpose of this study was to investigate and compare the time motion and notational variables of 21 point singles` badminton play and of the old scoring system (15 points for males and 11 for females). Sixteen (8 males and 8 females) state-level badminton players with a mean age of 15.7 ± 1.2 years participated in this study. They were initially tested using incremental treadmill test following Bruce protocol to obtain individual maximum oxygen consumption (VO2max) value. VO2max of the male and female participants were 47.1 ± 5.2 ml·kg-1·min-1 and 39.8 ± 6.2 ml·kg-1·min-1 respectively. On a separate day, they played a simulated badminton match using 21 points (Trial 1) and 15 / 11 points (Trial 2) scoring system. During the trials, a video camera was used for time-motion and notational analysis throughout the match. The statistical analysis showed that total number of shots and rallies in a match were the only variables which were significantly higher in the 15 points compared to 21 points in men`s singles match play [331.2 ± 51.6 vs 463.5 ± 24.7 (total shots) and 70.2 ± 1.2 vs 97 ± 6.6 (total rallies) respectively]. Even though female players had a greater point difference (10 points) in the new scoring system compared to the male counterparts, there were no significant differences in all parameters measured. The patterns of play which were analyzed on the basis of notational variables were also similar in both scoring systems. However, some differences in the time motion and notational analysis were found between genders suggesting that there should be different training regimens for men and women in their respective disciplines due to greater intensity, speed of play and the longer rally lengths in men`s singles. Therefore, it is recommended that players should impart more emphasis in the development and improvement of the skills/techniques rather than making any drastic changes to the training programme to develop their physical fitness to meet the demands of the match with the 21 point scoring system.